2011
DOI: 10.1128/iai.00980-10
|View full text |Cite
|
Sign up to set email alerts
|

Native Properdin Binds toChlamydia pneumoniaeand Promotes Complement Activation

Abstract: Activation of complement represents one means of natural resistance to infection from a wide variety of potential pathogens. Recently, properdin, a positive regulator of the alternative pathway of complement, has been shown to bind to surfaces and promote complement activation. Here we studied whether properdinmediated complement activation occurs on the surface of Chlamydia pneumoniae, an obligate intracellular Gram-negative bacterium that causes 10 to 20% of community-acquired pneumonia. We have determined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 56 publications
3
49
1
5
Order By: Relevance
“…Recent studies have shown that surface-bound P can act as a platform to assemble new C3 convertases and initiate AP complement activation (23, 33, 6366). Although direct binding of plasma P to host cells in the absence of deposited C3b has not been demonstrated, newly released P from activated neutrophils was found to be capable of binding to apoptotic cells and trigger AP complement activation (40, 67).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that surface-bound P can act as a platform to assemble new C3 convertases and initiate AP complement activation (23, 33, 6366). Although direct binding of plasma P to host cells in the absence of deposited C3b has not been demonstrated, newly released P from activated neutrophils was found to be capable of binding to apoptotic cells and trigger AP complement activation (40, 67).…”
Section: Discussionmentioning
confidence: 99%
“…In a non-serum environment, binding of purified properdin to Neisseria gonorrhoeae and Chlamydophila pneumoniae was claimed to stimulate alternative pathway activation by recruiting C3b and C3 H2O , which, upon addition of FB and FD, formed C3bBb convertases [33,34]. Whereas properdin did not bind to wild-type Escherichia coli or Salmonella enterica serovar Typhimurium strains, it did bind to mutants lacking the O-antigens of their lipopolysaccharides (LPS).…”
Section: Recognitionmentioning
confidence: 99%
“…Historically, P n was referred to as “activated P” because unlike the native P 2 -P4 it caused AP complement activation and C3 consumption when added to normal serum (Farries et al, 1987). Using freshly separated P, it was demonstrated that P 2 -P 4 could bind specifically to zymosan, necrotic Raji and Jurkat cells and Chlamydia pneumoniae , but not to rabbit erythrocytes or live cells (Cortes et al, 2011; Ferreira et al, 2010). In contrast, P n or unfractionated P bound to almost all AP activating cells or surfaces tested (Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, P n or unfractionated P bound to almost all AP activating cells or surfaces tested (Ferreira et al, 2010). Notably, even though purified native P2-P4 was able to bind Chlamydia pneumonia , no P binding could be detected using human serum in the presence of EDTA (Cortes et al, 2011). Similarly, Agarwal et al found that while serum P played a critical role in AP complement activation and killing of diverse strains of Neisseria meningitidis and Neisseria gonorrhoeae , purified native P 2 -P 4 did not bind to any of the strains.…”
Section: Introductionmentioning
confidence: 99%